2020
DOI: 10.1111/iere.12493
|View full text |Cite
|
Sign up to set email alerts
|

Homeownership and Housing Transitions: Explaining the Demographic Composition

Abstract: We document the evolution of homeownership rate across various age groups for the period 1995-2015. We find that variations in the homeownership rates are relatively large for the young, which is mostly driven by renter-to-owner transitions. In order to explain these empirical facts, we consider a life-cycle model featuring housing tenure decisions. Housing is modeled as an indivisible and lumpy investment subject to both loan-tovalue (LTV) and debt-to-income (DTI) credit constraints and transaction fees. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We take the parameters that govern the idiosyncratic income process from Kaplan et al (2020a) , who set the persistence of the log-AR(1) shocks and the standard deviation of innovations . The deterministic life-cycle profile of income follows a simple tent shape, following ( Ma and Zubairy, 2021 ): where is the peak age for earnings, and captures the rise in earnings over the life-cycle. We set the peak earnings age to be 50 ( ), and so that, on average, labour income rises by 50 percent between entering the labor force and the peak earnings age.…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…We take the parameters that govern the idiosyncratic income process from Kaplan et al (2020a) , who set the persistence of the log-AR(1) shocks and the standard deviation of innovations . The deterministic life-cycle profile of income follows a simple tent shape, following ( Ma and Zubairy, 2021 ): where is the peak age for earnings, and captures the rise in earnings over the life-cycle. We set the peak earnings age to be 50 ( ), and so that, on average, labour income rises by 50 percent between entering the labor force and the peak earnings age.…”
Section: Calibrationmentioning
confidence: 99%
“…The lack of substantial amplification may seem surprising since falling mortgage rates loosen PTI constraints on mortgage borrowing, and so could potentially relax borrowing constraints at the same time as the stay-at-home shock increases housing demand. To understand why the interaction between lower mortgage rates and the stay-at-home shock does not have a quantitatively large effect in the model we compute the share of marginal house buyers for whom the PTI constraint dominates the LTV constraint, following Ma and Zubairy (2021) . We define a marginal house buyer as a household whose value of purchasing a house is very close to the value of renting: A marginal buyer is then PTI-dominant if the amount that can be borrowed at the maximum PTI constraint is less than the amount that can be borrowed at the maximum LTV constraint: where is the average house size chosen by households in steady state.…”
Section: Pandemic Experiments In the Quantitative Modelmentioning
confidence: 99%
“…This is because small changes in household incomes or in mortgage interest rates immediately affect the PTI constraint. Ma and Zubairy (2021) explicitly compare the relative importance of LTV and PTI constraints for the household transition from renting to owning. They show that PTI type constraints are much more important for explaining home ownership decisions for young households.…”
Section: Borrowing Constraint Factorsmentioning
confidence: 99%
“…The fixed retirement income replacement rate of 65 per cent is the average Australian replacement rate as reported by the OECD (OECD Publishing 2020). We use the same lifecycle profile of income as Ma et al (2021), where income grows by 50 per cent from age 20 to age 50, and then falls at the same rate until retirement. Labour income has a random component and as is standard in the literature, we assume that the random component of income during working life follows an auto-regressive process of order one .…”
Section: Model Calibrationmentioning
confidence: 99%
“…By the life cycle model, Ruan et al (2020) showed house prices are closely related to the leverage ratio of the residential sector and there is a significant self-reinforcing effect between them, which will magnify the impact on major macroeconomic variables, such as consumption and investment [36]. Ma and Zubairy (2020) claimed that due to the mechanism of collateral constraint, financial leverage will exert a non-negligible impact on consumption, investment, and total social output by acting on collateral prices (mainly house prices and stock prices) [37].…”
Section: Theoretical Analysismentioning
confidence: 99%